2018
DOI: 10.1166/jnn.2018.14284
|View full text |Cite
|
Sign up to set email alerts
|

MD Simulation on Collision Behavior Between Nano-Scale TiO2 Particles During Vacuum Cold Spraying

Abstract: Particle collision behavior influences significantly inter-nano particle bonding formation during the nano-ceramic coating deposition by vacuum cold spraying (or aerosol deposition method). In order to illuminate the collision behavior between nano-scale ceramic particles, molecular dynamic simulation was applied to explore impact process between nano-scale TiO2 particles through controlling impact velocities. Results show that the recoil efficiency of the nano-scale TiO2 particle is decreased with the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…[45] However, results of this study can only be taken into account partially in our study, since the impact of nanoparticles was simulated, and nanoparticles usually get deflected by the stagnation point flow in the real application and cannot reach the substrate at all. [46][47][48][49][50] Recently, two significant experimental and simulative contributions toward a better understanding were made by Lee et al [51] and Furuya et al [52] Lee et al [51] observed a cushioning effect on ductile substrate materials: particles that hit the ductile substrate first will be less fragmented than those that hit later. Therefore, the ceramic film near the substrate has a lower density (or more voids) than in an area further away from the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] However, results of this study can only be taken into account partially in our study, since the impact of nanoparticles was simulated, and nanoparticles usually get deflected by the stagnation point flow in the real application and cannot reach the substrate at all. [46][47][48][49][50] Recently, two significant experimental and simulative contributions toward a better understanding were made by Lee et al [51] and Furuya et al [52] Lee et al [51] observed a cushioning effect on ductile substrate materials: particles that hit the ductile substrate first will be less fragmented than those that hit later. Therefore, the ceramic film near the substrate has a lower density (or more voids) than in an area further away from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 ] However, results of this study can only be taken into account partially in our study, since the impact of nanoparticles was simulated, and nanoparticles usually get deflected by the stagnation point flow in the real application and cannot reach the substrate at all. [ 46–50 ] Recently, two significant experimental and simulative contributions toward a better understanding were made by Lee et al. [ 51 ] and Furuya et al.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations offer possibilities to understand the CGDS bonding mechanisms at an atomistic level under the conditions of some macro experimental parameters [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], which will verify these experimental parameters through pure theoretical methods, without any uncontrollable factor, and optimize or simplify the existing experiments. Higher incident velocities, larger particle sizes and higher temperatures could improve the overall bonding strength between the clusters and substrates, such as the elements Cu and Au [14,15], and Ni and Ti [16].…”
Section: Introductionmentioning
confidence: 99%
“…The higher bonding strength and compatibility of Pd and Cu were expressed by the larger interfacial bonding energy and interfacial shearing strength at the Pd-Cu composite metal membrane (CMM) interface [24]. The bonding formation mechanism for nanoscale ceramic particle (TiN or TiO 2 ) collision was largely determined by the relationship between the adhesion energy and the rebound energy, and the nanoscale ceramic particles could be bonded together, as the adhesion energy was higher than the rebound energy [25][26][27]. Recently, the metallurgical bonding mechanism of the nano-scale ceramic particle (TiO 2 ) was verified by the atomic displacement and lattice distortion, which was specifically due to the debonding of oxygen atoms from TiO 2 and bonding with Ti atoms in the substrate [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some scholars and researchers have made progress in simulating cold spray process by MD method. For instance, Yao et al have simulated collision behavior between nano-scale TiO2 particles during cold spray [21] and Joshi et al modeled the whole cold spray process in nanometer dimension [22]. These studies investigated the bonding mechanism in cold spray process and understood the effect of critical parameters including impact velocity, angle and particle size.…”
Section: Introductionmentioning
confidence: 99%